Applications, Pollution, Toxicity and Bioremediation of Acrylamide (Journal of Environmental Microbiology and Toxicology, 2019)
Acrylamide has many chemical and environmental uses. The main or principle use of acrylamide is in the production of high molecular weight polyacrylamides with up to 99.9% of acrylamide is estimated used to produce polyacrylamide. Acrylamide, in the form of polyacrylamides are used as binders and retention supports for fibres and to retain pigments on paper fibres, to decrease soil erosion, in furrow irrigation systems and in the formulation for the herbicide glyphosate. Acrylamide is a neurotoxic agent and its pollution remains an important global awareness due to its acute toxicity. Due to its toxicity, the maximum permissible limit for acrylamide containing in drinking water of Malaysia is 0.0005 mg/L. Its uses, toxicity, pollution and bioremediation are the subject of this mini review.
Keywords: Acrylamide; Polyacrylamide; Toxicity; Pollution; Bioremediation